2002
DOI: 10.1016/s0035-9203(02)90084-2
|View full text |Cite
|
Sign up to set email alerts
|

Traditional use of mosquito-repellent plants in western Kenya and their evaluation in semi-field experimental huts against Anopheles gambiae: ethnobotanical studies and application by thermal expulsion and direct burning

Abstract: Ethnobotanical survey in 2 communities in western Kenya revealed that the most commonly known repellent plants were Ocimum americanum L. (64.1%), Lantana camara L. (17.9%), Tagetes minuta L. (11.3%) and Azadirachta indica A. Juss (8.7%) on Rusinga Island, and Hyptis suaveolens Poit. (49.2%), L. camara (30.9%) and O. basilicum L. (30.4%) in Rambira. Direct burning of plants is the most common method of application for O. americanum (68.8%), L. camara (100%) and O. basilicum (58.8%). Placing branches or whole pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 10 publications
12
118
0
6
Order By: Relevance
“…A very similar result has been found in a study conducted in rural areas of Papua New Guinea (Paul et al, 1995) and Kenya (Seyoum et al, 2002). Those results are in line with the habits many communities living in rural areas have to use aromatic smokes in addition to wood smoke -i.e.…”
Section: Vector Densitysupporting
confidence: 89%
“…A very similar result has been found in a study conducted in rural areas of Papua New Guinea (Paul et al, 1995) and Kenya (Seyoum et al, 2002). Those results are in line with the habits many communities living in rural areas have to use aromatic smokes in addition to wood smoke -i.e.…”
Section: Vector Densitysupporting
confidence: 89%
“…[57] Mosquitoes do not bite 52% and 39% of those who use Saccharum officinarum and Ocimum basilicum (traditional plant repellents) respectively in Cameroon. [57] Similar studies have been reported in Kenya [56,58] and soap-form ("Faso Soap") repellents has also proven effective in Burkina Faso. [59] Although, rural communities have the skills to prepare, it is considered laborious, [56] making it less organisationally feasible.…”
Section: Strategies To Address Community Educationmentioning
confidence: 53%
“…(Gu et al, 1988) and Hypericum calcyinum L. (Decosterd et al, 1991) have shown in vivo and in vitro activity Kirkia wilmsii 3.7 No previous reports of antiplasmodial activity Lippia javanica 3.8 Reported to be a mosquito repellent (Govere et al, 2000), but no previous reports of antiplasmodial activity Ocimum americanum a 4.2 Used as a mosquito repellent (Seyoum et al, 2002) (Alves et al, 1997;Oketch-Rabah et al, 1998;Abosi and Raseroka, 2003;Kraft et al, 2003) …”
Section: Resultsmentioning
confidence: 99%